2016
DOI: 10.1038/srep24834
|View full text |Cite
|
Sign up to set email alerts
|

Glucose becomes one of the worst carbon sources for E.coli on poor nitrogen sources due to suboptimal levels of cAMP

Abstract: In most conditions, glucose is the best carbon source for E. coli: it provides faster growth than other sugars, and is consumed first in sugar mixtures. Here we identify conditions in which E. coli strains grow slower on glucose than on other sugars, namely when a single amino acid (arginine, glutamate, or proline) is the sole nitrogen source. In sugar mixtures with these nitrogen sources, E. coli still consumes glucose first, but grows faster rather than slower after exhausting glucose, generating a reversed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 63 publications
(76 reference statements)
5
98
0
1
Order By: Relevance
“…In the three cases, no L-arginine production was detected, showing that glutamate is not suitable as the sole nitrogen source. Poor growth of a variety of E. coli strains on glucose when glutamate (at about 1.5 g/L) was the sole nitrogen source has been reported in a recent study [38]. It has been observed that under those conditions, TCA cycle intermediates accumulate, leading to the inhibition of the signalling molecule cAMP levels, thereby impairing cell growth.…”
Section: Comparison Of Nitrogen Sourcesmentioning
confidence: 96%
See 1 more Smart Citation
“…In the three cases, no L-arginine production was detected, showing that glutamate is not suitable as the sole nitrogen source. Poor growth of a variety of E. coli strains on glucose when glutamate (at about 1.5 g/L) was the sole nitrogen source has been reported in a recent study [38]. It has been observed that under those conditions, TCA cycle intermediates accumulate, leading to the inhibition of the signalling molecule cAMP levels, thereby impairing cell growth.…”
Section: Comparison Of Nitrogen Sourcesmentioning
confidence: 96%
“…These results therefore indicate that a C/N ratio of 12 provides insufficient nitrogen for efficient fermentation. In the fermentation with 30 g/L glucose, the cells used the remaining glucose after cell growth and L-arginine production stopped, likely due to utilization of L-arginine as a poor nitrogen source (L-arginine concentration is decreasing) [38], and only acetate was produced. In the fermentation with 15 g/L glucose, neither glucose uptake nor acetate production occurred after ammonia depletion.…”
Section: Comparison Of C/n Ratiosmentioning
confidence: 99%
“…One prediction from this picture is that the growth rate is optimal under all conditions that respect the growth laws and that sub-optimal resource allocation only occurs, when cells deviate from these laws. Previous studies identified conditions of sub-optimal growth in E. coli , but did not address this sub-optimality in the context of growth laws131415 or focused specifically on conditions that do not follow the growth law16, so that it remains unclear whether growth laws maximize the growth rate. A second possible explanation for growth laws is that they are practical heuristics: the growth law line is determined by cellular regulation and not by optimality constraints.…”
mentioning
confidence: 99%
“…Under most circumstances, glucose is a preferred carbon source for Escherichia coli, yet under some conditions, metabolic flux becomes suboptimal, and glucose transport and metabolism are disfavored (1,2). One condition of impaired glucose metabolism occurs when cells are exposed to nonmetabolizable glucose analogs (e.g., ␣-methylglucoside [␣MG]) that are taken up and phosphorylated but cannot be metabolized further.…”
mentioning
confidence: 99%
“…A previous study demonstrated that the IIC Glc domain of PtsG most likely confers substrate specificity for glucose. In that study, a chimeric transporter composed of the PtsG 2 , and the total number of spots was determined and plotted as heat maps. Cells are combined from two independent experiments.…”
mentioning
confidence: 99%